Pregnancy and COVID-19 pandemic: Impacts on the maternal-fetal binomial (Research, Society and Development, 2021)
The aim of this study is to reveal the impacts of the COVID-19 pandemic on pregnancy. The article adopted the systematic review model, using the SciELO, PubMed and Google Scholar databases, using the descriptors “Coronavirus” and “Pregnancy”. Twenty complete articles were selected, published since 2020 to the present moment. It was noticed that pregnancy is a unique immunological state, in which physiological and mechanical changes occur in the maternal-fetal interface, which makes pregnant women more susceptible to viral infections. Thus, with the pandemic of COVID-19, although studies do not show that pregnant women present a greater deterioration of the clinical picture when compared to the general population, changes were observed that may imply gestational complications, such as pre-eclampsia, prematurity, early rupture of membrane and perinatal death. Thus, it is important to pay attention to this group, focusing on alarm signals for cases of moderate to severe involvement, with provision of clinical support, through hospitalization in isolation, adequate nutrition, supply of supplemental oxygen (if necessary) , observing fluid and electrolyte intake, as well as monitoring vital signs of mother and fetus. In addition, the performance of prenatal, intrapartum and postpartum should not be excluded, but adjusted. In situations of suspicion or confirmed infection, it is recommended that scheduling appointments and procedures be postponed for at least 7 days, up to 14 days; and telemedicine is an option to prioritize the health of pregnant women and social isolation.